Kontribusi Dana Bagi Hasil Pajak Dan Dana Bagi Hasil Bukan Pajak/Sumber Daya Alam Terhadap Dana Perimbangan Provinsi Sumatera Utara - Simbolon, Indah Sari; Siregar, Zulkifli; Apriandi, Azhar (Universitas Islam Sumatera Utara, 2025)
This research aims to determine the effect of tax revenue sharing funds and nontax revenue sharing funds on balancing funds in North Sumatra Province in a quantitative descriptive manner. The data analysis technique used in this research is multiple linear regression analysis with the help of the IBM SPSS statistics 25 application. The results of this research show that the tax revenue sharing fund variable does have a significant effect on balancing funds seen from tcount > ttable (6,438 > 1.895) and the significant level is greater than 0.05 (0.468 > 0.05), and the research results of the variable non-tax profit sharing funds/SDA have effect on balancing funds seen from tcount > ttable (2,339 >1.895) and the significance level is greater than 0.05 (9,425 > 0.05). The research results together show that the tax profit sharing fund variable and the non-tax profit sharing fund variable have effect on balancing funds seen from the value of Fcount > Ftable (1.036 < 4,74).